2018
DOI: 10.15171/hpr.2018.27
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary/Involuntary Admissions/Readmissions of Psychiatric Patients in a University Hospital in Turkey From 2008 to 2016

Abstract: Background:The treatment and hospitalization of psychiatric patients has been a dilemma for many years. Many countries have different specific legislations regarding the hospitalization and treatment of mental patients.Objective: In the current study, 4100 voluntary/involuntary psychiatric admissions and readmissions to a university hospital in Turkey were investigated, and patient groups were compared in terms of demographic variables and psychiatric diagnoses based on DSM IV-TR. Methods: The records of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…On this basis, it could be considered that, compared to the past or other countries, the diagnosis of severe mental disorder in Cyprus is taking place at an early stage, and subsequently effective treatment is applied, thus restraining possible cognitive implications of severe mental disorders 47 − 48 . The relationship between education level and involuntary admission and/or readmission for compulsory treatment reported herein is also confirmed by other studies 27 . Previous data show an increased incidence of admissions in high security units for compulsory treatment in those with postgraduate education, and in particular holders of diplomas in vocational specializations 3,29,30,43,45,52,56 . This may suggest that in some countries the majority of mental health service users are integrated into professional specialization programmes, which enables them to acquire vocational skills and further prevent occupational exclusion, social isolation and selfstigmatisation 58 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On this basis, it could be considered that, compared to the past or other countries, the diagnosis of severe mental disorder in Cyprus is taking place at an early stage, and subsequently effective treatment is applied, thus restraining possible cognitive implications of severe mental disorders 47 − 48 . The relationship between education level and involuntary admission and/or readmission for compulsory treatment reported herein is also confirmed by other studies 27 . Previous data show an increased incidence of admissions in high security units for compulsory treatment in those with postgraduate education, and in particular holders of diplomas in vocational specializations 3,29,30,43,45,52,56 . This may suggest that in some countries the majority of mental health service users are integrated into professional specialization programmes, which enables them to acquire vocational skills and further prevent occupational exclusion, social isolation and selfstigmatisation 58 .…”
Section: Discussionmentioning
confidence: 98%
“…Special focus needs to be given in the sub-group of individuals with psychotic symptoms, and mainly schizophrenia and relevant psychotic disorders. Overall, the present study confirmed previous data which show that those with schizophrenia and relevant psychotic disorders are more often involuntary hospitalized 27−38 . Furthermore, additional emphasis needs to be given on educational programmes in pharmacotherapy and treatment options in order to enhance adherence to therapy, since the main cause of relapse herein as well as internationally seems to be non-adherence to pharmacotherapy 27 − 31,39−40 . As for other risk factors for involuntary admission and subsequent compulsory treatment, male gender has been well documented in international literature 3,[28][29][32][33][34][35][36][37][38][41][42][43][44][45][46][47][48][50][51] . Yet, other studies present data which report increased frequency of compulsory treatment among females 9,30,[52][53]55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation